Estudio de factibilidad para la implementación de la tecnología BIG DATA en el departamento de sistemas de la Universidad Técnica de Babahoyo - Mastian Sisa, Edgar Fabricio (2020)
Big Data refers to countless data that come from different sources such as: web and social networks, machine-to-machine, transactions, biometrics, generated by people and generated by organizations, which are highly complex when analyzed. , which through the use of this technology we can acquire a better understanding, in order to obtain valuable information for entities and organizations, which in their time can make better decisions. To carry out this feasibility study for the implementation of Big Data technology in the university's systems department, I used the hypothetical deductive methodology since it is the method that allows me to reach a conclusion by means of a hypothesis, but then it could be verified; The interview technique was used, which served to establish the environment in which the systems department is managed; and in turn the tool called interview was used, through this tool we obtained a dialogue with the person in charge of the department and in this way we were able to gain an in-depth understanding of the advantages and disadvantages of the institution's digital platform.